Pengembangan Trainer Pengontrolan Elektromagnetik Pada Jurusan Teknik Instalasi Tenaga Listrik di Smk Negeri 2 Peureulak Ã¢â¬â Aceh Timur - Pratama, Hendri (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
Department of Electrical Installation Engineering at SMK Negeri 2 Peureulak is part of educational institutions whose graduates are required to have the expertise and creativity. Various school efforts prepare learners to be ready to work by providing a provision of competence in accordance with their respective vocational fields. Competencies obtained by students are tailored to industry-based curriculum criteria so that they have ready-made expertise through the learning process. Learning tools or media used in the learning process has an important role to bridge the learning objectives to be achieved. Therefore, the learning media used is very influential on the intensity of learners on the subject matter taught. One form of learning media commonly used in SMK level can be a trainer that is expected to support the learning process especially to understand the working principles and functions of an electrical control installation in the industry. Trainers are designed using a modular concept that each component is made separately, equipped with component names, symbols and manuals of use so that it can easily be introduced to components, use and facilitate understanding of the concept of electromagnetic control installations. The design and manufacture of this trainer through several stages of the material and information gathering stage, the design of each component module, the design of sliding frames and storage boxes, tool making, tool testing and the last manual book making. The research method used is research and development method (Research & Development). There are three steps to determine the eligibility of the electromagnetic control trainers, namely (1) the manufacture of electromagnetic control trainers (2) the trainer feasibility test (3) product testing. In this study that acts as respondents are 3 teachers and 23 students technical expertise program electrical installation in SMK Negeri 2 Peureulak. Research instrument used in the form of questionnaire of media feasibility test, student response questionnaire and observation sheet. The results showed that the electromagnetic control trainer that has been developed feasible to be used as instructional media of electromagnetic control in electrical engineering skill program at SMK Negeri 2 Peureulak. The achievement of feasibility of trainer can be seen from the result of feasibility analysis by expert team which get the percentage of 81% with good category, and the result of student response to the electromagnetic control trainer get the percentage of 87% with very good category. There was a significant difference between the learners learning outcomes between before and after using trainers, where the average practice value before using the trainer was 77.81 and after trainer use increased to 82.30.